Pengaruh Kompetensi Sumber Daya Manusia (SDM), Penerapan Sistem Akuntansi Keuangan Daerah, dan Penerapan Standar Akuntansi Pemerintah (SAP) Terhadap Kualitas Laporan Keuangan Daerah Pada Pemerintah Provinsi Riau (Studi Empiris Pada SKPD Provinsi Riau) - Liza Rahayu; Kennedy '; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims are to analyze empiricly the impact of competence, Public Accounting System, and Public Accounting Standar partially to the Public Financial Statement Quality at Riau Province Government. The population of this research are 39 work unit i.e. Riau Province Secretary, Riau Provinsi Secretary Council, and others units, to analyzed the data is use multiple regression method.The result of this study are competence, Public Accounting System, and Public Accounting Standar have a significant effect to the Public Financial Statement Quality, it can be seen by the t-test > t tabel.Keyword: Competence, Public Accounting System, Public Accounting Standar Public Financial Statement Quality